Obstetric and perinatal outcome in previous one cesarean section - Patel, Seema; Kansara, Vijay; Patel, Riddhi; Anand, Nikhil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Women with previous cesarean sections constitute a high risk group in obstetrics, with associated complications. The cesarean section carries 3 fold risk of mortality compared with vaginal deliveries. The study was conducted to determine the mode of deliveries after previous one cesarean section, maternal and fetal complication. Methods: This is a prospective observation study. Total 150 patients of previous one caesarean with gestational weeks between 37 to 40 weeks admitted in labour room of Obstetrics and Gynecology Department in Sola Civil Hospital with spontaneous onset of labour, over a period of one year from April 2014 to April 2015 or till the desired sample will reached. Results: In the present study, out of 150 pregnant women with history of previous one LSCS who were subjected to this study, 39(26%) underwent elective LSCS, commonest indication being previous pregnancy bad experience (38.46%). 111(74%) underwent trial of labour after cesarean section out of it 77(69.36%) had successful VBAC and 34(30.63%) underwent repeat emergency LSCS. Maternal complications were higher in Emergency LSCS group than in those had a successful VBAC (17.64% vs.3.89%)). Neonatal complications were also higher in Emergency LSCS group than in those had a successful VBAC (2.95% vs. 0%). Conclusions: With proper case selection, appropriate timing and close supervision trial of labour after prior LSCS is safe and often successful.